Grand Intentions, Small Interventions: Climate Data Rescue as Counter-Data Action - Paris, Britt S; Currie, Morgan; Donovan, Joan (AoIR Selected Papers of Internet Research, 2017)
Anticipating the incoming Trump administration’s hostility to climate science, the University of Toronto launched the first “data rescue” event in December 2016, creating a template for a kind of activism it labeled “guerilla archiving” to describe volunteers’ tactics of seeding, scraping, and bagging to disperse federal scientific climate data, documents, and webpages into an international patchwork of repositories. In recent months, similar events cropped up across the United States, guided by the Environmental Data Governance Initiative’s (EDGI) Data Rescue efforts. The need for such work became palpable as official statements on anthropogenic climate change began disappearing from governmental websites, within hours of Trump’s inauguration ceremony. “Guerilla archiving” is a neologism – a critical term missing from archival literature. This paper examines Data Rescue’s guerrilla archiving efforts to situate the term within archival and critical data discourses and highlight its novelty as a contemporary case of both. Archiving in the face of political expediency is common in many types of radical archival projects. However, while radical archival work seeks to pluralize a community’s narrative through alternate stories and interpretations, EDGI’s web archiving and mirroring pluralizes and distributes the material context of the data. It distributes the data as a public good, generating occasions for data literacy projects which re-envision power and political action related to these datasets. In this sense, “guerilla archiving” exists as a unique example of counter-data action and statactivism, as it imagines new interventions to reconfigure power through distributed data management and use.